Preliminary Studies on the fluctuation of the biomass of sizefractionated zooplankton in sea grass bed of Pulau Tinggi, Malaysia - Shuaib, Nasir; Mohamed, Maryati; Rusiman, Mohd Saifullah; Matias- Peralta, Hazel Monica; Abdur Rahim, Abdur Rahim (2020)
Zooplanktons biomass was extensively studied in the sea grass bed of Pulau Tinggi, Malaysia for six months. In 2015, sampling months were April, June, October, whereas in 2016, April, June, August were the sampling months. A cone shaped plankton net was used with 0.30 m mouth, 1.00 m length and 100 μm mesh size. The fractionation of zooplankton size was carried out in to >2000 μm (large), 501-2000 μm (medium) and <500 μm (small). Zooplankton was classified as copepods, larvaceans, chaetognaths, cnidarians, ctenophores, decapods and polychaetes. Copepods were categorized as Calanoida, Poecilostomatoida, Cyclopoida and Harpacticoida but identified as a total of 54 species, 26 genera and 19 families. We conclude that among the biomass of 3 size fractions; medium (36%) was dominant followed by large and small (32% each) throughout the study period.